Psychotic reactions to daily life stress and dopamine function in people with severe hearing impairment. Issue 8 (June 2015) - Gevonden, M. J.; Myin-Germeys, I.; van den Brink, W.; van Os, J.; Selten, J. P.; Booij, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. Minor stresses measured in daily life have repeatedly been associated with increased momentary psychotic experiences, both in individuals with psychotic disorders and in persons who are genetically at an increased risk for these disorders. Severe hearing impairment (SHI) is an environmental risk factor for psychotic disorder, possibly due to the experience of social exclusion. The aim of the current study is to investigate whether people with SHI exhibit higher levels of psychotic reactivity to social stressors in daily life than normal-hearing controls and whether this reactivity is associated with decreased baseline dopamine (DA) D2/3 receptor availability and/or elevated DA release following a dexamphetamine challenge. Method. We conducted an experience sampling study in 15 young adults with SHI and 19 matched normal-hearing controls who had previously participated in a single photon emission computed tomography study measuring DA D2/3 receptor availability and DA release in response to dexamphetamine. Results. The association between social stress and momentary psychotic experiences in daily life was stronger among SHI participants than among normal-hearing controls. Interactions between social stress and baseline striatal DA D2/3 receptor availability or DA release were not significant in multilevel models of momentary psychotic experiences including age, sex and tobacco use. Conclusions. While both elevated striatal DA release and elevated psychotic stress reactivity have been found in the same population defined by an environmental risk factor, SHI, their inter-relationship cannot be established. Further research is warranted to clarify the association between biological and psychological endophenotypes and psychosis risk.